The Impact of Bank Competition on Stability in Central Asia: The Moderating Role of Bank Digitalization - Begimkulov, Emil; Kuti, Mónika (Public Finance Quarterly, 2025)
This study investigates the impact of bank competition on financial stability in the Central Asian banking sector, with a focus on the moderating role of bank digitalization. The research addresses a critical question—whether digitalization reinforces or weakens the stabilizing effects of competition—in a region characterized by early-stage digital adoption and concentrated markets. Given the growing reliance on technology in banking, understanding its role in shaping risk dynamics is both scientifically relevant and practically important for policymakers and financial institutions. The study employs dynamic panel data analysis using the two-step GMM estimator. Bank stability is measured using the z-score, Competition is assessed through the Panzar-Rosse Model, and digitalization is captured via a composite index. The results reveal that bank competition improves stability, while digitalization alone initially increases risk due to operational vulnerabilities. However, the interaction between competition and digitalization has a positive and stabilizing effect, enhancing risk management and efficiency. These findings highlight the transformational role of digitalization, emphasizing the need for balanced competition policies and support for digital adoption to ensure financial stability in emerging markets.